Cross-section measurements of the Higgs boson decaying into a pair of T-leptons in proton-proton collisions at vs =13 TeV with the ATLAS detector - Aaboud, Morad; Anders, Christoph; Andrei, George Victor; Antel, Claire; Baas, Alessandra Edda; Bolz, Arthur; Brandt, Oleg; Britzger, Daniel; Djuvsland, Julia Isabell; Dunford, Monica; Ferreira de Lima, Danilo Enoque; Franchino, Silvia; et al. (Physical review, 2019)
A measurement of production cross sections of the Higgs boson in proton-proton collisions is presented in the H→ττ decay channel. The analysis is performed using 36.1 fb−1 of data recorded by the ATLAS experiment at the Large Hadron Collider at a center-of-mass energy of √s=13 TeV. All combinations of leptonic (τ→ℓv¯v with ℓ=e,μ) and hadronic (τ→hadrons v) τ decays are considered. The H→ττ signal over the expected background from other Standard Model processes is established with an observed (expected) significance of 4.4 (4.1) standard deviations. Combined with results obtained using data taken at 7 and 8 TeV center-of-mass energies, the observed (expected) significance amounts to 6.4 (5.4) standard deviations and constitutes an observation of H→ττ decays. Using the data taken at √s=13 TeV, the total cross section in the H→ττ decay channel is measured to be 3.77+0.60−0.59 (stat) +0.87−0.74 (syst) pb, for a Higgs boson of mass 125 GeV assuming the relative contributions of its production modes as predicted by the Standard Model. Total cross sections in the H→ττ decay channel are determined separately for vector-boson-fusion production and gluon-gluon-fusion production to be σVBFH→ττ=0.28±0.09 (stat) +0.11−0.09 (syst) pb and σggFH→ττ=3.1±1.0 (stat) +1.6−1.3 (syst) pb, respectively. Similarly, results of a fit are reported in the framework of simplified template cross sections. All measurements are in agreement with Standard Model expectations.
ATLAS Collaboration: M. Aaboud, C. Anders, G.V. Andrei, C. Antel, A.E. Baas, A. Bolz, O. Brandt, D. Britzger, J.I. Djuvsland, M. Dunford, D.E. Ferreira de Lima, S. Franchino, M.P. Geisler, M. Giulini, P. Hanke, J. Jongmanns, M. Kolb, A. Kugel, M. Lisovyi, H. Meyer zu Theenhausen, F. Napolitano, D.I. Narrias Villar, M. Sahinsoy, A. Schöning, H.-C. Schultz-Coulon, T. Spieker, R. Stamen, P. Starovoitov, S. Suchek, J. Wang, S. Weber, M. Wessels, X. Yue [und weitere]
Gesehen am 26.06.2019